Strategy of Drought Disaster Mitigation in North Central Timor District, East Nusa Tenggara Province, Indonesia - Sinta Setyawati; Ardiyanto Maksimilianus Gai; Ida Soewarni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Drought is a natural disaster that threatens and disrupts people's lives, where the demand for water remains constant or even increases, while groundwater reserves decrease, leading to insufficient water availability for daily needs. To formulate an effective drought disaster mitigation strategy, an analysis of the drought disaster risk level must first be conducted. Mapping disaster risk areas plays a crucial role in supporting effective decision-making for disaster management. In line with the research objectives, the paradigm of disaster risk, disaster mitigation, and drought-related theories can be synthesized into several indicators for determining drought disaster risk levels. As the dry season progresses, North Central Timor Regency experiences severe drought, resulting in water availability falling far below the required levels for domestic use, agriculture, the economy, and the environment. Residents are forced to purchase water tanks to irrigate their drying rice fields and buy drum water daily to meet their household needs. This study employs both qualitative and quantitative research methods. The disaster risk level is formulated using Delphi analysis and the Analytical Hierarchy Process (AHP), while the identification of drought disaster mitigation strategies is conducted through descriptive analysis.